2019
DOI: 10.1002/pca.2816
|View full text |Cite
|
Sign up to set email alerts
|

TLC‐bioautography identification and GC‐MS analysis of antimicrobial and antioxidant active compounds in Musa × paradisiaca L. fruit pulp essential oil

Abstract: Introduction The absence of microbial growth and resistance to oxidative deterioration in fruits of Musa × paradisiaca L. (bananas) is an indication of the presence of antimicrobial and antioxidant metabolites. Objective In order to investigate the secondary metabolomic spectrum as well as the active antimicrobial and antioxidants present in essential oils (EOs) from fruits of different geographical areas of M. × paradisiaca, gas chromatography‐mass spectroscopy (GC‐MS) principal component data correlation ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 34 publications
1
21
0
1
Order By: Relevance
“…In the case of the ethanol extract, antifungal activity against Candida albicans was observed. The current observed antimicrobial activity of M. paradisiaca fruit stalk extracts against oral pathogens implicated in oral infections complements that of other studies which showed that extracts from fruits, florets, root, leaves, and peels of M. paradisiaca possess antimicrobial properties [ 23 , 27 , 33 , 34 ]. The current observation together with that of previous studies which demonstrated that M. paradisiaca has antimicrobial activity against A. actinomycetemcomitans [ 35 ] and C. albicans [ 23 ] clearly shows the possible prospects of M. paradisiaca as an alternative or complementary oral therapy that can be exploited for use by indigenous people.…”
Section: Discussionsupporting
confidence: 85%
“…In the case of the ethanol extract, antifungal activity against Candida albicans was observed. The current observed antimicrobial activity of M. paradisiaca fruit stalk extracts against oral pathogens implicated in oral infections complements that of other studies which showed that extracts from fruits, florets, root, leaves, and peels of M. paradisiaca possess antimicrobial properties [ 23 , 27 , 33 , 34 ]. The current observation together with that of previous studies which demonstrated that M. paradisiaca has antimicrobial activity against A. actinomycetemcomitans [ 35 ] and C. albicans [ 23 ] clearly shows the possible prospects of M. paradisiaca as an alternative or complementary oral therapy that can be exploited for use by indigenous people.…”
Section: Discussionsupporting
confidence: 85%
“…Because of the antimicrobial activity of its components (32)(33)(34), TTO exhibits in vitro antimicrobial activity (35).…”
Section: Discussionmentioning
confidence: 99%
“…Terpinen-4-ol accounts for nearly 60% of the major components of TTO. Because of the antimicrobial activity of its components ( 32 34 ), TTO exhibits in vitro antimicrobial activity ( 35 ). In the current study, we revealed TTO in vivo may be a potential alternative to antibiotics in weanling pigs.…”
Section: Discussionmentioning
confidence: 99%
“…To screen metabolites possessing antibacterial activity, a TLC bioautography was performed. The active zone on certain Rf value will appear if the spots contain certain levels of antibacterial compounds [23,24]. In this study, the comparison Rf values of patches that have activity against S. aureus or E. coli as well as the positive control (chloramphenicol 0.675 mg) is depicted in fig.…”
Section: Antibacterial Activity Of Extractmentioning
confidence: 99%